Integration of voluntary male medical circumcision for HIV prevention into norms of masculinity: findings from Kisumu, Kenya. Issue 10 (1st October 2021) - Fleming, Paul J.; Doshi, Monika; Harper, Gary W.; Otieno, Frederick; Bailey, Robert C.
Abstract: While it is clear that in many communities ideas about masculinity and circumcision are connected, it is still unclear how young Kenyan men in the former Nyanza province from the traditionally non-circumcising Luo people perceive voluntary medical male circumcision as connected to masculinity and the role of voluntary medical male circumcision in the transition from boyhood to manhood. The objective of this study was to explore norms of masculinity and the decision-making process among Luo young men to provide a better understanding of how circumcision and masculinity relate to cultural norms within this community. The methodology consisted of eight FGDs with male peer groups and 24 in-depth interviews to elicit young men's perceptions of masculinity and voluntary medical male circumcision. Findings from thematic analysis reveal that young men described several key characteristics of masculinity including responsibility, bravery and sexual attractiveness. For some young men, voluntary medical male circumcision has embedded itself into cultural norms of masculinity by being a step in the transition from boyhood to manhood and by being a marker of some of these masculine characteristics. In the case of voluntary medical male circumcision, there may be opportunities to integrate other programming that helps men transition into healthy adulthood.